IMPLEMENTASI PEMBELAJARAN DALAM JARINGAN BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) PADA MATA PELAJARAN IPS KELAS V DI SDIT AL IZZAH - Ery Luluk Sa'adah; Ujang Jamaludin; Ikman Nur Rahman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study was to provide an overview of the implementation of the learning based on Higher Order Thinking Skills (HOTS) for social science subject at grade V, especially when learning was conducted online. HOTS-based learning began to be applied when the 2013 curriculum was refined. Therefore, schools in Indonesia started to implement HOTS-based learning in order that the students achieved a superior level of thinking. In addition, the refinement of the 2013 curriculum has also been linked to smart predictions occurred in the 21st century, in which everything is based on students, for example how students build their skills to live and work, to innovate, and skills to manage technology. These skills are related to everyday life in which a person performs social activities. This social life is summarized in Social Sciences (IPS) subject taught to students in elementary schools. Social science subject is influential in educating the students since the materials are very helpful for the students to understand their world. However, students are candidates of the society, so that provision is crucial before they start to socialize. IPS is presented to provide learning on order to fulfill their social nature as humans or social beings.